Epiphytic bacteria from flowers and fruits as potential probiotics: A systematic review - Migdalia Sarahy Navidad-Murrieta; Francia G. López-Cárdenas; Pablo Rufino-Marcelino; Manuel I. Girón-Pérez; Víctor M. Zamora-Gasga; Adrián Hernández-Mendoza; Sonia G. Sáyago-Ayerdi (Food Chemistry Advances)
In recent years, the isolation and identification of epiphytic bacteria from flowers and fruits have become essential study areas. Investigating lactic acid bacteria (LAB) uncovers previously unexplored niches, potentially discovering unique species or strains with significant environmental and technological applications. This research can contribute to developing new and improved food products with enhanced organoleptic properties, nutritional content, and shelf life. Although reports of LAB from flowers and fruits remain scarce, they have been shown to produce metabolites of interest with potential impacts on post-harvest control, environmental interactions, and applications in both the food industry and gut health.Therefore, this systematic review aims to compile the most recent research and provide an overview of the current state-of-the-art on the relationship between LAB, their use, and multiple applications; to contribute to a better understanding of the role of potential epiphytic bacteria.